Strategic Analysis of Bath & Body Works, Inc in the US market - Paing, Thae Thae; Kubíček, Aleš; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor’s thesis provides a comprehensive strategic analysis of Bath & Body Works, Inc., a leading American retailer specializing in personal care and home fragrance products. The primary objective of this study is to evaluate the company's internal resources, external environment, and strategic positioning in the increasingly competitive U.S. personal care market. The analysis is grounded in various strategic frameworks, including PEST, Porter’s Five Forces, SWOT, VRIO, and performance benchmarking, providing insights into the company’s strengths, weaknesses, opportunities, and threats. Findings highlight the impact of shifting consumer preferences, digital transformation, and operational restructuring following the company’s separation from L Brands in 2021. The thesis concludes with strategic recommendations for improving brand differentiation, supply chain localization, and personalized customer engagement to maintain sustainable growth and competitiveness in the evolving market.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses